Superior Character Education, Ki Hadjar Dewantara's Paradigm for the Ideal PAI Teacher - Nazahah Ulin Nuha; Khozen; Nurhakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this research is to understand the concept of character education thought according to Ki Hajar Dewantara and the role of PAI teachers in its formation, with the purpose of applying it in the context of contemporary education faced with various challenges of values and morals. This research uses a qualitative approach, through library research, by collecting books on Ki Hajar Dewantara as primary sources, as well as journals and articles as secondary sources. This data is then analyzed to reach a conclusion. The restriction of this research focuses on Ki Hajar Dewantara's thoughts related to character education, especially superior character and the concept of an ideal PAI teacher. The results show that Ki Hajar Dewantara's thoughts on character education emphasize maximum efforts in building and strengthening personality, while teachers act as facilitators and examples in shaping character. This study describes the development process of Ki Hajar Dewantara's thought, explains its relevance to current conditions, and analyzes its relevance to the role of PAI teachers. The implementation of this thought is expected to bring society towards a better life.